Telomeres and Estrogens: The Unholy Nexus in Pathogenesis of Atherosclerosis - Sameer, Aga Syed (Cardiol Res, 2014)
Atherosclerosis (AS) is a complex inflammatory process and is categorized as a multifactorial disease involving the interplay of genetic and environmental factors. There are many factors which play role in predisposition and development of AS. In this review we have tried to address the basic pathophysiology of AS lesions and the role played by two important factors - telomeres and estrogens in the development of this disease.